2022
DOI: 10.1002/smtd.202101435
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Technologies for the On‐Chip Integration of 2D Materials

Abstract: The carrier mobilities of all the listed materials are experimental results except for those of SnSe, MoO 3 , MoSSe, WSSe, and graphdiyne that are theoretical calculated values; b) The n, k values for all the listed materials are at 1550 nm except for BP at 800 nm and h-BN at 1200 nm; c) The NLO parameters of PdSe 2 , PtSe 2 , BP, h-BN, MoO 3 , and CsPbBr 3 are at 800 nm. Those of MoS 2 and Bi 2 Te 3 are at 1060 nm. Those of other materials are at 1550 nm. In addition to third-order optical nonlinearity, stron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 594 publications
1
53
0
Order By: Relevance
“…Next, a 1.5-μm thick silica upper cladding layer was deposited using plasma enhanced chemical vapor deposition (PECVD), followed by opening a window on it down to the BOX layer via photolithography and reactive ion etching processes. Finally, the 2D layered GO film was coated onto the SOI nanowires by using a solution-based method that enabled transfer-free and layer-by-layer film coating, as reported previously [ 45 , 46 , 47 , 48 ]. Compared to the sophisticated and cumbersome film transfer processes (e.g., manipulation with scotch tape) used for other 2D materials such as graphene and transition metal dichalcogenides (TMDCs) [ 36 , 37 , 49 ], our GO coating method shows advantages in achieving highly scalable fabrication, precise control of the layer number (i.e., film thickness, with a high resolution of ~2 nm), and conformal film attachment onto integrated devices [ 41 , 47 ].…”
Section: Device and Characterizationmentioning
confidence: 99%
“…Next, a 1.5-μm thick silica upper cladding layer was deposited using plasma enhanced chemical vapor deposition (PECVD), followed by opening a window on it down to the BOX layer via photolithography and reactive ion etching processes. Finally, the 2D layered GO film was coated onto the SOI nanowires by using a solution-based method that enabled transfer-free and layer-by-layer film coating, as reported previously [ 45 , 46 , 47 , 48 ]. Compared to the sophisticated and cumbersome film transfer processes (e.g., manipulation with scotch tape) used for other 2D materials such as graphene and transition metal dichalcogenides (TMDCs) [ 36 , 37 , 49 ], our GO coating method shows advantages in achieving highly scalable fabrication, precise control of the layer number (i.e., film thickness, with a high resolution of ~2 nm), and conformal film attachment onto integrated devices [ 41 , 47 ].…”
Section: Device and Characterizationmentioning
confidence: 99%
“…Further recent theoretical work has shown that these results can be significantly improved, [42][43][44][45][46][47] aided by sophisticated integration methods. [48] This work will potentially have significant implications for on-chip microcombs and their applications. In summary, our results verify the enhanced nonlinear optical performance of nanowires, waveguides, and ring resonators achievable by incorporating 2D layered GO films.…”
Section: Discussionmentioning
confidence: 99%
“…A silica upper cladding was then deposited using high-density plasma-enhanced chemical vapor deposition (HDP-PECVD), followed by opening a window on it down to the top surface of the Si 3 N 4 waveguides via lithography and reactive ion etching (RIE). Finally, the 2D layered GO lm was coated onto the Si 3 N 4 waveguide by using a solutionbased method that enabled transfer-free and layer-by-layer lm coating, as reported previously [45][46][47]49].…”
Section: Device Fabrication and Characterizationmentioning
confidence: 99%
“…Enhanced SPM has been demonstrated in integrated waveguides incorporating graphene [36][37][38], MoS 2 [39], WS 2 [40], and graphene oxide (GO) [41]. Amongst the different 2D materials, GO has shown many advantages for implementing hybrid integrated photonic devices with superior SPM performance, including a large Kerr nonlinearity (about 4 orders of magnitude higher than Si [42,43]), relatively low loss compared to other 2D materials (over 2 orders of magnitude lower than graphene [44,45]), facile synthesis processes [46,47], and high compatibility with CMOS fabrication [48,49]. In our previous work [41], we demonstrated enhanced SPM of picosecond optical pulses in Si waveguides integrated with 2D GO lms, achieving a maximum spectral broadening factor (BF) of ~4.3 and enhanced FOM by up to 20 times.…”
Section: Introductionmentioning
confidence: 99%